ANALISIS KONTRASTIF KATA SAPAAN/PANGGILAN DALAM KELUARGA PADA BAHASA SUNDA DAN BAHASA INDONESIA - Nurkaila Navita; Arum Handayani; Odien Rosidin (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to explore the form and use of kinship greeting terms in Sundanese and Indonesian through the contrastive analysis method. The methodology used is a qualitative approach with data collection techniques using interviews with two informants from Pandeglang Regency, coupled with a literature review from various written sources. The findings of this study indicate that although both languages have a similar kinship framework, there are significant differences in aspects of greeting forms, social functions, and contexts of use. Sundanese has a higher complexity, is hierarchical, and is highly dependent on context, taking into account elements of age, emotional ties, and social status. Meanwhile, Indonesian applies a more neutral, formal, and uniform greeting system. The study also found changes in the use of traditional greeting terms among the younger generation, caused by the influence of formal education, mass media, and advances in digital communication. This study emphasizes that differences in greeting systems not only reflect the structure of the language, but also reflect the cultural values that underlie social interaction in society. These findings have important implications for the fields of language education, preservation of cultural heritage, and intercultural communication in Indonesia.